Little Book, Big Waves: The Epistle of James and Global Stewardship in Bioethics - Lora Jean Brake (Sekolah Tinggi Theologia Jaffray, 2016)
At first glance the twenty-first century arena of biotechnology and bioethics seems worlds away from the practical concerns of the first century outlook of the New Testament book of James. A closer look, however, reveals that the issues that James addresses have applications to challenges in bioethics. This article will give an overview of James and examine James’ teaching on wealth, poverty, and generosity and its import for the issue of global stewardship in bioethics. Stewardship concerns both a Christian’s care and management of time, talents, and treasures. Faithful use of the resources God has given demonstrates the fruitful faith that James writes of in his epistle. The idea of global stewardship, though “stewardship” is grounded in a distinctly Christian ethic, reflects an emerging discussion in bioethics regarding the need to address the inequities present between the money and time spent on biotechnology in some of the world in proportion to the money spent on meeting the basic healthcare needs of the poor of the entire world. This New Testament epistle gives clear indications of how the Christian is to view wealth and how the Christian is to respond to poverty. James, though a comparatively small book, sends a crucial message across the years that should greatly impact how Christians view stewardship in terms of global healthcare needs.